Diversity of endophytic bacteria and microfungi in Syzygium cumini fruit from West Java, Indonesia - IDA INDRAWATI; NIA ROSSIANA; Muhammad Faizal Fathurrohim (Society for Indonesian Biodiversity, 2021)
Abstract. Rossiana N, Fathurrohim MF, Indrawati I. 2021. Diversity of endophytic bacteria and microfungi in Syzygium cumini fruit from West Java, Indonesia. Biodiversitas 22: 3943-3948. Syzygium cumini L. Skells is a native evergreen tropical tree in Southeast Asia belong to the Myrtaceae family, known as the Java plum, jambul, jambolan, jamblang, or jamun. The bacterial and fungal endophytes associated with fruit have not been determined and functionally characterized. The endophytic microbes live inside the surface-sterilized fruits and have no visibly harmful effects on the plants. The purposes of the study were to isolate, characterize, and determine the diversity of endophytic bacteria and fungi in S. cumini fruit. The endophytes from S. cumini fruit were observed morphologically for identification. The result of isolation and identification showed there are four bacterial isolate endophytes (B. cereus, B. subtilis, B. megaterium, and Bacillus sp.) and four fungal endophytes (Candida guilliermondii, Penicillium sp., Mycelia sterilia, and Aspergillus sp.) isolated from S. cumini fruit. Keywords:Biodiversity, Bacterial endophyte, Fungi endophyte, Jamblang